Ancaman Sampah Impor bagi Keamanan Manusia: Studi Kasus Desa Bangun dan Tropodo 2018-2019 - Novaradila, Gresika; Ali, Yusril Ihza; Astin, Lila Afifa; Aryani, Maria Indira; Purwanto, Aldira Mara Ditta Caesar (Global and Policy Journal of International Relations, 2020)
ABSTRACT The National Sword Policy implemented by the Chinese Government in 2018 has a spillover effect in several countries in the Asian region, especially Indonesia. As one of the importers of recycled paper waste, Indonesia is faced with the problem of hazardous waste from abroad, which has increased by two percent in 2018. Besides, Indonesia also does not have good waste management, which exacerbates environmental damage and pollution. some of them were experienced by Bangun and Tropodo Villages in East Java. The level of environmental pollution in Bangun and Tropodo Villages is quite high as a result of being used as a final disposal site for paper raw material waste mixed with foreign waste and hazardous toxic materials. As a result, environmental crises continue to occur and affect the quality of life of the people. This study analyzes the correlation between environmental crises which is directly proportional to the increasing threat to human security. The environmental crisis due to imported waste can turn into a security threat issue through the securitization process carried out by NGOs and the government. The author uses the concept of human security and securitization theory to see the causality relationship. In the end, the state is not only faced with traditional security problems that are territorial but problems of individual human security. Indonesia was forced to change several waste import policies. Keywords: Imported Waste, Environmental Crisis, Securitization, Human Security. Kebijakan National Sword Policy Pemerintah Tiongkok pada tahun 2018 memberikan efek spillover pada beberapa negara di kawasan Asia, khususnya Indonesia. Sebagai salah satu importir sampah kertas daur ulang, Indonesia dihadapkan dengan masalah sampah bahan berbahaya dari luar negeri hingga terjadi peningkatan sebesar dua persen pada tahun 2018. Selain itu, Indonesia juga masih belum memiliki manajemen pengelolaan sampah yang baik sehingga memperparah pada kerusakan dan pencemaran lingkungan yang beberapa di antaranya dialami oleh Desa Bangun dan Tropodo di Jawa Timur. Tingkat pencemaran lingkungan Â Desa Bangun dan Tropodo cukup tinggi akibat dijadikan sebagai tempat pembuangan akhir bagi sampah bahan baku kertas yang bercampur dengan sampah luar negeri dan bahan beracun berbahaya. Sebagai imbasnya, krisis lingkungan terus terjadi dan mempengaruhi kualitas hidup masyarakat. Penelitian ini menganalisis korelasi antara krisis lingkungan yang berbanding lurus dengan peningkatan ancaman terhadap keamanan manusia. Krisis lingkungan akibat sampah impor dapat berubah menjadi isu ancaman keamanan melalui proses sekuritisasi yang dilakukan oleh NGO dan pemerintah. Penulis menggunakan konsep keamanan manusia dan teori sekuritisasi untuk melihat hubungan kausalitas. Pada akhirnya, negara tidak hanya dihadapkan dengan masalah-masalah keamanan tradisional yang bersifat teritorial melainkan masalah keamanan manusia yang bersifat individu. Indonesia terpaksa mengubah beberapa kebijakan impor sampah. Kata kunci: Sampah Impor, Krisis Lingkungan Hidup, Sekuritisasi, Keamanan Manusia